Derivatives - David A. Dubofsky (Oxford University Press, 2003)
Derivatives: Valuation and Risk Management, by David A. Dubofsky and Thomas W. Miller, Jr., enables students to acquire a strong working knowledge and thorough understanding of the rapidly growing field of financial derivatives. Students will learn essential risk management skills, such as how markets in these securities can be used to shift risk away from or toward the user...